Recobrimentos de ligas Ti-Nb-Zr depositados por pulverização magneto-catódica sobre aço inoxidável AISI 316L para aplicações biomédicas - Lemos, Lucas Leal D'Azevedo (Universidade Federal de São Carlos, 2022)
The work consists of the deposition of Ti-Nb-Zr ternary alloy coatings in the form of thin films on an AISI 316L stainless steel substrate for applications in the biomedical area, such as dental or orthopedic prosthesis. The main goal of this study is the production of a material with a lower manufacturing cost, when compared to the bulk material composed only by the Ti-Nb-Zr alloy. In addition to this factor, the biocompatibility of the Ti-Nb-Zr alloy is superior to that of AISI 316L steel. The deposition technique used in this work is magnetron sputtering”) using three targets, one of titanium and the others by niobium and zirconium, and stainless steel as substrate. The coatings are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled with X-ray energy dispersive spectroscopy (EDS), and X-ray excited photoelectron spectroscopy (XPS) to obtain the composition, crystallographic, morphological and texture properties. Mechanical tests are also carried out, such as nanoindentation, to evaluate the properties of the deposited material and its compatibility with human tissue. The results from this work indicate that design and evaluation of Ti based thin films can be achieved by methods such as Bo-Md diagram and molybdenum equivalency. Young’s modulus for all samples in this work have presented lower values compared to 316L stainless steel, what corroborates its application as a material for orthopaedic prosthesis.
Ti-Nb-Zr alloy coatings deposited by magnetron sputtering on AISI 316L stainless steel
Keywords: Recobrimentos; Ligas à base de titânio; Biomateriais; Filmes finos metálicos; Pulverização magneto-catódica; Coatings; Titanium based alloys; Biomaterials; Metallic thin films; Magnetron sputtering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA